ANALISIS PRINSIP KERJA PROSES CHARGE DAN DISCHARGE PADA CAPASITOR DENGAN RANGKAIAN RC - WILMAR SIAGIAN (JURNAL ILMIAH SIMANTEK, 2020)
The purpose of this research is to: to know the characteristics of charge and discharge processes on thecapacitor. Based on the results of the analysis of data done, the conclusion that: the capacitor voltage graph onthe capacitor Pegisian indicates that the current rises linearly until it reaches and the voltage rises exponentially(curved upwards) when passing  = RC. The current graph on the capacitor filling indicates that the current dropslinearly to reach  = RC and the current drops exponentially (curved downward) after passing  = RC. Thecapacitor voltage graph on discharge capacitor indicates that the voltage drops down linearly until it reaches the = RC and the voltage drops exponentially (curve down) after passing  = RC. The current chart on the capacitordischarge indicates that the current drops linearly to reach  = RC, and the current drops exponentially (downwardcurve) after passing the  = RC. After the charging period is equal to 4 time constants (4T), the capacitor on theRC circuit is considered already in full state and the voltage passing the Capacititorworth 99% of the maximumvalue, 0, 99 . The time it takes for the capacitor to reach this state is called the Transient Period. After reaching 5time constants (5T) The capacitors are completely in full state and the voltage that passes through the capacitorequals the voltage at the power supply. In these circumstances, there is no current flowing in the RC circuit,so this condition is called the Steady State Period.